Ommatophoca rossii Gray 1844 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ommatophoca rossii Gray 1844 Ommatophoca rossii Gray 1844, Zool. Voy. H. M. S. "Erebus" and "Terror", Vol. 1: 3. Type Locality: "Antarctic ocean", restricted by Barrett-Hamilton (1902) to "pack ice, north of Ross Sea 68°S, 176°E ". Vernacular Names: Ross Seal. Distribution: Circumpolar, Antarctic pack ice, particularly King Haakon VII Sea. Vagrant populations on Heard Isl and S Australia. Conservation: IUCN – Lower Risk (lc). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 598, DOI: 10.5281/zenodo.7316519